Amorphous Iron(III)‐Borate Nanolattices as Multifunctional Electrodes for Self‐Driven Overall Water Splitting and Rechargeable Zinc–Air Battery. Issue 48 (27th September 2018) - Zhao, Weinan; Xu, Tao; Li, Tao; Wang, Yuankun; Liu, Hui; Feng, Jianze; Ding, Shujiang; Li, Zhongtao; Wu, Mingbo
Abstract: Highly stable and low‐cost electrocatalysts with multi‐electrocatalytic activities are in high demand for developing advanced energy conversion devices. Herein, a unique trifunctional amorphous iron‐borate electrode is developed, which is capable of boosting hydrogen evolution, oxygen evolution, and oxygen reduction reactions simultaneously. The amorphous iron borate can self‐assemble into well‐defined nanolattices on electrode surface through a facile hydrothermal process, which possess more active sites and charge transfer pathways. As a result, the asymmetry overall water‐splitting cell that adopts the amorphous electrodes as anode and cathode can be driven at 1.56 V with the current density of 10 mA cm −2, which is lowest in state‐of‐the‐art catalysts. Moreover, the water‐splitting devices can be powered by a two‐series‐connected amorphous electrode–based zinc–air battery with high stability and Faradic efficiency (96.3%). The result can offer a potential and promising alternative way to develop metal‐borate electrode for multifunctional applications. Abstract : A new type multifunctional electrode of amorphous Iron(III)‐borate nanolattices, vertical grown on Ni foam, is successfully synthesized. Carefully experiments, multiple application, and theoretical analysis discover that iron borate with high intrinsic activity can provide a new material using in various energy conversion and storage devices.